Komisija za resnico in pričevanje Rigoberte Menchú Tum v antropološki presoji - Kralj, Gašper (Družboslovne razprave, 2005)
In this article we analyze truth commissions, standard procedures in countriesin transition from authoritarian to "democratic" regimes, and the testimony of Rigoberta Menchú Tum, one of the best-known indigenous woman in Latin America. Thus we expose two intertwined problems of strategic representations of violence and terror. On the one hand, how personal testimonies, autobiographical narratives, and oral histories, through the imputation of unintelligible pain into the official histories of nation-states, became part of everyday social reality and eurocentric perceptions of former colonies. In other words, why after reading an extensive report of the Truth Commission we are left with the impression that the administration of mass death over indigenous was almost inevitable. On theother hand, it would be unsuitable to overlook how such representations of violence and terror encountered active resistance precisely in societies with alternative sources of communal adaptation. Following the testimony of Rigoberta Menchú we pose the question how individual testimonies step into wider historical counter-narrations and what they do. In contrast to intellectual dynamics in Mexico where anthropologists in accordance with the political ideology of indigenism almost "successfully" imputed indigenous pasts into the national heritage of the "mestico- nation" the parallel process of "ladinoization" in Guatemala encountered active resistance from Mayan intellectuals and supporting activists. But, since the icon of their struggle within the cognitive restrictions and institutional barriers of the humanitarian organizations has been transformed into the paradigmatic victim, she has been distanced from the popular movement.
Keywords: Menchú Tum, Rigoberta; Guatemala; Gvatemala; etnične skupine; staroselci; socialna antropologija; kolonializem; nasilje; asimilacija; assimilation; človekove pravice; human rights